1997
DOI: 10.1159/000121160
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Circulation Aneurysms in a Child: Clipping of One Leads to Spontaneous Thrombosis of the Other

Abstract: Multiple intracranial aneurysms in children are infrequent. This case involves an 11-year-old girl who presented with subarachnoid hemorrhage with posterior cerebral and superior cerebellar artery aneurysms. Initially, she underwent clipping of the posterior cerebral artery aneurysm. Four months later, she returned for clipping of the other aneurysm, at which time it was found to have completely thombosed. The literature contains 4 other cases of spontaneous thrombosis of intracranial aneurysms in children, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…2;14;15 Spontaneous thrombosis of the cerebral aneurysm Spontaneous thrombosis of a cerebral aneurysm in a child is rare, particularly of a non-giant aneurysm. 16 Nanda and Drury 16 reviewed 28 cases of spontaneously thrombosed aneurysms and stated that the tendency of giant aneurysms to spontaneously thrombose is related to the size ratio of the aneurysm to its neck, haemodynamic considerations and the age of the aneurysm. The role of SAH in spontaneous thrombosis is controversial.…”
Section: Aneurysms Of the Distal Aca In Infancymentioning
confidence: 99%
See 2 more Smart Citations
“…2;14;15 Spontaneous thrombosis of the cerebral aneurysm Spontaneous thrombosis of a cerebral aneurysm in a child is rare, particularly of a non-giant aneurysm. 16 Nanda and Drury 16 reviewed 28 cases of spontaneously thrombosed aneurysms and stated that the tendency of giant aneurysms to spontaneously thrombose is related to the size ratio of the aneurysm to its neck, haemodynamic considerations and the age of the aneurysm. The role of SAH in spontaneous thrombosis is controversial.…”
Section: Aneurysms Of the Distal Aca In Infancymentioning
confidence: 99%
“…The role of SAH in spontaneous thrombosis is controversial. 16 Spetzler et al 17 reported an adult case of an aneurysm that repeatedly disappeared and reappeared on serial angiography. Though they hesitated to present a conclusion on the pathogenesis of this phenomenon, they did refer to the possible effect of the e-aminocaproic acid or of marked vasospasm.…”
Section: Aneurysms Of the Distal Aca In Infancymentioning
confidence: 99%
See 1 more Smart Citation